Britain and the sea of darkness: Islandology in al-Idrīsī's Nuzhat al-Mushtaq. Issue 4 (December 2016) - Chism, Christine
Abstract This paper argues that al-Idrīsī's geography, while pursuing the sovereign interests of the Norman king of Sicily, Roger II, nonetheless critiques Norman empire-building using insular tropes and littoral uncertainty in his description of Britain and the other countries of the seventh climate.